2005
DOI: 10.1002/pmic.200401123
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of anti-Francisella tularensis LVS antibody response in murine model of tularemia

Abstract: Francisella tularensis live vaccine strain infection of mice has been established as an experimental model of tularemia that is suitable for studies of immune mechanisms against the intracellular pathogen. In this study, the model was used to explore immunogenic repertoire of F. tularensis with the aim of identifying new molecules able to activate the host immune system, potential bacterial markers with vaccine, and diagnostic applications. Immunoproteomic approach based on the combination of two-dimensional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 56 publications
5
67
0
Order By: Relevance
“…The latter study identified a larger number of potential OMP candidates, approximately 500 in total, yet only 4 were predicted to be OMPs, including FopA. In an effort to identify immunogenic proteins from F. tularensis, total cellular proteins were separated by 2DE and probed with sera from experimentally infected mice (19). Of the 36 immunoreactive proteins identified, the vast majority were probable cytoplasmic proteins, whereas only two predicted OMPs were noted.…”
mentioning
confidence: 99%
“…The latter study identified a larger number of potential OMP candidates, approximately 500 in total, yet only 4 were predicted to be OMPs, including FopA. In an effort to identify immunogenic proteins from F. tularensis, total cellular proteins were separated by 2DE and probed with sera from experimentally infected mice (19). Of the 36 immunoreactive proteins identified, the vast majority were probable cytoplasmic proteins, whereas only two predicted OMPs were noted.…”
mentioning
confidence: 99%
“…Cross-reactions are possible only with serum obtained from patients with brucellosis or yersiniosis, but sera with a titer lower than 1:320 do not agglutinate Brucellae at all [129,197]. The agglutination test can be followed by the Rose Bengal plate test, which is often used as a rapid screening test in the diagnosis of brucellosis [198], or, according to our experience, with immunoproteomic techniques to exclude cross-reactions [194].…”
Section: Diagnosis Detection and Laboratory Confirmationmentioning
confidence: 99%
“…Among these are antibodies oriented against some outer membrane proteins such as FopA, OmpA [192,193], and Tul4 [194]; against other intracellular proteins such as GroEL, KatG [192], and DnaK; and against several putative virulence markers such as nucleoside diphosphate kinase, isocitrate dehydrogenase, the RNA-binding protein Hfq, and the molecular chaperone ClpB [194,195]. Thus, antibodies can potentially contribute to the protective response by eliminating Francisella virulence factors and, together with the antibody-independent functions of B cells, can demonstrate the potential of B cells to collaborate with T cells in the induction, regulation, and expression of protective immunity against F. tularensis infection.…”
Section: Host Immune Responsementioning
confidence: 99%
“…Finally, ABAYE3267 protein sequence is similar to a highly conserved protein, the nucleoside diphosphate kinase (NDK) that is present in a number of bacteria including Bacillus anthracis, Francisella tularensis and Campylobacter fetus and considered to be a potential virulence target and thus a vaccine candidate. [54][55][56] Using the MBGD platform, 34 the proteomic data of OMVs obtained from HPLC/MS/MS experiments and bioinformatics prediction of surface-exposed antigens, we have identified 77 antigens as potential vaccine candidates ( Table S2). The final list was restricted to 13 putative antigens.…”
mentioning
confidence: 99%